Validation of corner beam-column joint’s hysteresis loops between experimental and modelled using HYSTERES program / N.F. Hadi...[et al.] - N.F., Hadi,; M., Mohamad; N.H., Hamid (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The beam - column joint is an important part of a multi-storey RC building as it caters for lateral and gravitational load during an earthquake event. The beam-column joints should have a medium to high ductility for transferring the earthquake load and gravity load to the foundation. By designing multi-storey RC buildings using Eurocode 8 can avoid any diagonal shear cracks in column which is a major problem in non-seismic design buildings using British Standard (BS8110). This paper presents the experimental hysteresis loops of monolithic corner beam-column joints of multi-storey building which had been designed using Eurocode 8 and tested under in-plane lateral cyclic loading. The experimental hysteresis loops of corner beam-column joint was compared with modelled using the HYSTERES program. The full-scale corner beam-column joint of a two story precast school building was designed, constructed, tested and modelled is presented herein. The seismic performance parameters such as lateral strength capacity, stiffness, ductility and equivalent viscous damping were compared between experimental and modelled hysteresis loops. The experimental hysteresis loops have similar shape with the modeling hysteresis loops with small percentage differences between them.